Correction: The impact of COVID-19 on sexual risk behaviour for HIV acquisition in east Zimbabwe: An observational study. - Rebekah Morris; Simon Gregson; Rufurwokuda Maswera; Louisa Moorhouse; Tawanda Dadirai; Phyllis Mandizvidza; Brian Moyo; Owen Mugurungi; Constance Nyamukapa (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0003194.].